Possible frequent multiple mitochondrial DNA copies in a single nucleoid in HeLa cells - Pavluch, Vojtěch; Špaček, Tomáš; Engstová, Hana; Dlasková, Andrea; Ježek, Petr (Scientific reports, 2023)
Previously, a number of ~ 1.4 of mitochondrial DNA (mtDNA) molecules in a single nucleoid was reported, which would reflect a minimum nucleoid division. We applied 3D-double-color direct stochastic optical reconstruction microscopy (dSTORM), i.e. nanoscopy with ~ 25-40 nm x,y-resolution, together with our novel method of Delaunay segmentation of 3D data to identify unbiased 3D-overlaps. Noncoding D-loops were recognized in HeLa cells by mtDNA fluorescence in situ hybridization (mtFISH) 7S-DNA 250-bp probe, containing biotin, visualized by anti-biotin/Cy3B-conjugated antibodies. Other mtFISH probes with biotin or Alexa Fluor 647 (A647) against ATP6-COX3 gene overlaps (1,100 bp) were also used. Nucleoids were imaged by anti-DNA/(A647-)-Cy3B-conjugated antibodies. Resulting histograms counting mtFISH-loci/nucleoid overlaps demonstrated that 45% to 70% of visualized nucleoids contained two or more D-loops or ATP6-COX3-loci, indicating two or more mtDNA molecules per nucleoid. With increasing number of mtDNA per nucleoid, diameters were larger and their distribution histograms peaked at ~ 300 nm. A wide nucleoid diameter distribution was obtained also using 2D-STED for their imaging by anti-DNA/A647. At unchanged mtDNA copy number in osteosarcoma 143B cells, TFAM expression increased nucleoid spatial density 1.67-fold, indicating expansion of existing mtDNA and its redistribution into more nucleoids upon the higher TFAM/mtDNA stoichiometry. Validation of nucleoid imaging was also done with two TFAM mutants unable to bend or dimerize, respectively, which reduced both copy number and nucleoid spatial density by 80%. We conclude that frequently more than one mtDNA molecule exists within a single nucleoid in HeLa cells and that mitochondrial nucleoids do exist in a non-uniform size range.
Keywords: DNA vazebné proteiny; HeLa Cells; hybridizace in situ fluorescenční; DNA, Mitochondrial; lidé; HeLa buňky; Mitochondrial Proteins; In Situ Hybridization, Fluorescence; DNA-Binding Proteins; mitochondriální proteiny; mitochondriální DNA; Humans